2004
DOI: 10.1002/ar.a.20056
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nigella sativa on oxidative stress and β‐cell damage in streptozotocin‐induced diabetic rats

Abstract: The aim of the present study was to evaluate the possible protective effects of Nigella sativa L. (NS) against ␤-cell damage from streptozotocin (STZ)-induced diabetes in rats. STZ was injected intraperitoneally at a single dose of 50 mg/kg to induce diabetes. NS (0.2 ml/kg/day, i.p.) was injected for 3 days prior to STZ administration, and these injections were continued throughout the 4-week study. Oxidative stress is believed to play a role in the pathogenesis of diabetes mellitus (DM). To assess changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
110
1
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 169 publications
(133 citation statements)
references
References 39 publications
17
110
1
5
Order By: Relevance
“…Increased intensity of staining for insulin, and preservation of beta-cell numbers are apparent in the N. sativa treated diabetic rats. N. sativa treatment exerts a therapeutic protective effect in diabetes by decreasing oxidative stress and preserving pancreatic beta-cell integrity in STZ induced diabetes in rats [44]. Pari and Sankaranarayanan gave 20 -80 mg/ kg TQ intragastrically to STZ-nicotinamide induced diabetic rats for 45 days and observed its anti-hyperglycemic effect evidenced by decrease in glucose as well as HBA(1C) levels [45].…”
Section: Antidiabetic Activity In Stz Induced Diabetic Ratsmentioning
confidence: 99%
“…Increased intensity of staining for insulin, and preservation of beta-cell numbers are apparent in the N. sativa treated diabetic rats. N. sativa treatment exerts a therapeutic protective effect in diabetes by decreasing oxidative stress and preserving pancreatic beta-cell integrity in STZ induced diabetes in rats [44]. Pari and Sankaranarayanan gave 20 -80 mg/ kg TQ intragastrically to STZ-nicotinamide induced diabetic rats for 45 days and observed its anti-hyperglycemic effect evidenced by decrease in glucose as well as HBA(1C) levels [45].…”
Section: Antidiabetic Activity In Stz Induced Diabetic Ratsmentioning
confidence: 99%
“…In this present study, all groups had similar GPx1 immunolocalization in their livers, and GPx1 immunoreactivity levels of DM group was found to be in a few cells and weaker compared to the control group in accordance with previous studies. 47,48 Deprem et al 49 reported that capsaicin treatment decreased the GPx1 immunoreactivity in the liver of diabetic rats whereas Taşçı and Gülmez reported that melatonin treatment increased the GPx1 immunoreactivity in the liver. 48 In the present study, we found that GPx1 immunoreactivity in the liver of rats treated with Bryonia multiflora increased significantly compared to rats in the DM group.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes was induced in four groups by a single intraperitoneal (i.p) injection of STZ (50 mg/kg, freshly dissolved in 5 mmol/L citrate buffer, pH 4.5). [15,16] Two days after STZ treatment, the development of diabetes in four experimental groups was confirmed by measuring blood glucose levels in a tail vein blood samples. Rats with blood glucose levels of 250 mg/dL or higher were considered to be diabetic.…”
Section: Experimental Designmentioning
confidence: 92%